Association between pregnancy status and depressive symptoms in women aged 12 to 49 years in Peru: analysis of the ENDES 2018–2024 - Campaña Acuña, Andrés (2026)
Introduction: Depression in women of reproductive age affects pregnancy and requires timely population-based surveillance. Objectives: To evaluate the association between pregnancy and depressive symptoms and to identify sociodemographic, health, and household factors in Peru. Methods: Cross-sectional and analytical design including women aged 12 to 49 years from the Demographic and Family Health Survey (ENDES) 2018–2024. Exposure corresponded to current pregnancy. The outcome was depressive symptoms, measured as PHQ-9≥5 points. Sociodemographic, health, and household covariates were included. Crude and adjusted prevalence ratios (aPR) with 95% confidence intervals (95% CI) were estimated. Results: The analysis included 58,809 women. Depressive symptoms were associated with pregnancy (aPR=1.49; 95% CI 1.32–1.68; p<0.001), residence in Lima (aPR=1.05; 95% CI 1.00–1.11; p=0.044), the rich wealth index stratum (aPR=1.10; 95% CI 1.01–1.19; p=0.036), hypertension (aPR=1.53; 95% CI 1.41–1.66; p<0.001), diabetes (aPR=1.34; 95% CI 1.18–1.53; p<0.001), and alcohol consumption (aPR=1.17; 95% CI 1.09–1.24; p<0.001). Conversely, depressive symptoms were less frequent among women residing in rural areas (aPR=0.89; 95% CI 0.84–0.94; p<0.001), those with university education (aPR=0.62; 95% CI 0.51–0.77; p<0.001), and married women (aPR=0.69; 95% CI 0.66–0.72; p<0.001). Conclusion: Pregnancy is associated with a higher frequency of depressive symptoms, together with social and clinical factors, supporting screening and comprehensive care.